The Implementation of Religious Culture to Develop Students' Discipline Character - Ike Yuliani; Chusniatun Chusniatun (Electronic Journal of Education, Social Economics and Technology, 2025)
This study focuses on the implementation of religious culture in shaping the character of student discipline at SMA Batik 1 Surakarta. This study aims to analyze how the implementation of religious culture can shape the character of student discipline at SMA Batik 1 Surakarta. This study uses a qualitative descriptive method with data collection techniques through interviews, observations, and documentation. The subjects of the study included teachers and students. The results of the study indicate that religious culture at SMA Batik 1 Surakarta is implemented through daily programs, such as congregational prayer, Al-Qur'an tadarus activities, and Islamic attitude habits. This program not only instills religious values, but also shapes the character of student discipline, such as being on time, responsible, and committed to school rules. Supporting factors for the implementation of religious culture include support from the school, parents, and the surrounding environment, while the obstacles faced are ensuring student consistency in implementing religious culture outside of school.